Can Conferralism Account for Systemic Racism?. (3rd May 2022) - Ásta,
Abstract: Conferralism about race is a version of social constructivism about race, where the agents of construction seem to be individual agents. However, an important aspect of racism is systemic or structural, and seemingly not about the behavior of individual agents. Can conferralism account for that? In this paper, I begin to address that question by focusing on recent criticism of conferralism by Linda Martín Alcoff and Aaron Griffith.